Characteristics of Surkhondaryo's Art of Giving (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Through this article, we want to bring to the public the great service of the Sherabad school of epics in bringing our epics, which are a major genre of folklore, to the present day, and at the same time show that the efforts of our graduates from this school are meaningless.